Penerapan metode Inverse Distance Weighted (IDW) dalam interpolasi curah hujan (Studi kasus: Kabupaten Langkat) - Jose Carlos Tahitu; Jullia Titaley; Tohap Manurung (Fakultas Teknologi Informasi Universitas Kristen Satya Wacana, 2026)
This study aims to determine the optimal power value to be used in the interpolation of rainfall for the period 2023 in Langkat Regency using the Inverse Distance Weighted (IDW) method, with variations in the power value used being 1, 2, 3, 4, 5, and 6.8, and to explain the results of rainfall interpolation in Langkat Regency. The data used in this research are Langkat Regency rainfall data sourced from the Langkat Regency Central Statistics Agency, with a total of 25 observation points, distributed across the region. The results of this study indicate that the variation in power near the actual situation is 6.8, with a Root Mean Square Error (RMSE) of 49.99 mm/year. Based on the IDW interpolation results, the observation point with the highest rainfall is in Salapian District, and the lowest is in Pangkalan Susu District. These findings provide useful information for understanding rainfall distribution patterns in Langkat Regency.